Stress Analysis Around Tunnels During Construction Stages Using Finite Elements Method - Kais T. Shlash; Nahla M. Salim; Zainab H. Shaker (Engineering and Technology Journal, 2014)
In this study, the stresses around a tunnel during construction stages are discussed. For this purpose, the finite element method (FEM) was adopted as an effective approach to analyze the problem using (SIGMA/W) program. The research includes the study of the behavior of soil due to excavation of tunnel by calculating the displacements and stresses in three positions of tunnel (crown, wall, and invert) during the various stages of construction. The finite element analyses were carried out using (Elastic- plastic) and (linear elastic) models for the soil and the concrete liner respectively. From the results, it can be noticed that increasing the number of excavation stages (using six stages) decreases the displacement comparing with excavation using one stage.